Long-Term Outcomes of Tetralogy of Fallot Repair with Pulmonary Valve Preservation and with Transannular Patch - Borodinova, Olga S.; Mykhailovska, Anzhelika O. (Ukrainian Journal of Cardiovascular Surgery, 2025)
Introduction. Tetralogy of Fallot (ToF) is a prevalent cyanotic congenital heart defect, with surgical repair strategies focused on relieving right ventricular outflow tract obstruction (RVOTO). The choice between a transannular patch (TAP) and a valve-sparing non-transannular patch (NTAP) remains controversial due to the trade-off between pulmonary regurgitation and the risk of residual RVOTO. Aim. To evaluate the predictive value of intraoperative echocardiographic parameters – particularly the RVOT z-score – for identifying severe residual RVOTO in children with ToF and to analyse their long-term outcomes after ToF repair. Materials and Methods. This retrospective single-center study included 132 patients who underwent complete ToF repair. Intraoperative transesophageal echocardiography (ITEE) was used to assess RVOT anatomy and hemodynamics. The study assessed baseline characteristics and perioperative measurements of pulmonary valve (PV) and RVOT dimensions, pressure gradients, and long-term echocardiographic parameters. The primary endpoint was reoperation due to significant RVOTO. Statistical analysis included ROC curves, AUC calculation, threshold determination, sensitivity, and specificity. Group comparisons were performed using Student’s t-test or the Mann–Whitney U test, as appropriate. Results. NTAP was performed in 82.6 % and TAP in 17.4 % of patients. Patients in the TAP group had a significantly higher rate of RVOT-related reoperations (36.3 % vs 11.1 %; p = 0.0029), mainly due to severe pulmonary valve insufficiency and the need for RV–PA conduit implantation. The most accurate predictor of significant RVOTO requiring reintervention was an intraoperative RVOT z-score <-3.2, assessed by ITEE (AUC = 0.925; sensitivity 85.0 %, specificity 90.1 %). Other parameters, such as the Prv/Plv ratio, RV–PA gradients, and PV z-score, showed lower predictive accuracy. Conclusions. Reoperations on the RVOT were more common after TAP than NTAP (36.3 % vs 11.1 %, p = 0.0029), mainly due to residual RVOTO and PV insufficiency. An intraoperative RVOT z-score < -3.2 was the strongest predictor of significant RVOTO. Assessing RVOT and PV z-scores during surgery may help reduce reinterventions, support valve-sparing approaches, and lower the risk of late surgeries for PV insufficiency.